2020
DOI: 10.1055/a-1164-6791
|View full text |Cite
|
Sign up to set email alerts
|

Zur Therapie von Phylloides-Tumoren der Brust – eine Aufarbeitung von 66 Fällen mit Literaturübersicht

Abstract: ZusammenfassungPhylloides-Tumore (PT) der Brust werden anhand der Konstellation definierter histologischer Parameter als benigne, borderline und maligne klassifiziert. Die chirurgische Exzision ist die primäre Therapie, aber die Notwendigkeit zur Einhaltung bestimmter Sicherheitsabstände wird für alle drei Kategorien kontrovers diskutiert. Ziel der Arbeit ist eine kritische Stellungnahme zur bestehenden Empfehlung zu Sicherheitsabständen der Resektion.In unserem Brustzentrum wurden retrospektiv anhand der hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…En una revisión sistemática y metanálisis que tuvo como objetivo investigar las tasas de recurrencia local (LR) entre los tres tipos de tumores filoides, se obtuvo los siguientes resultados: La revisión incorporó 54 estudios con 9234 casos individuales. Las tasas de recurrencia fueron del 8 % para los filoides benignos, del 13 % para los limítrofes y del 18 % para los malignos (29).…”
Section: Resultsunclassified
“…En una revisión sistemática y metanálisis que tuvo como objetivo investigar las tasas de recurrencia local (LR) entre los tres tipos de tumores filoides, se obtuvo los siguientes resultados: La revisión incorporó 54 estudios con 9234 casos individuales. Las tasas de recurrencia fueron del 8 % para los filoides benignos, del 13 % para los limítrofes y del 18 % para los malignos (29).…”
Section: Resultsunclassified
“…Although several studies have shown that additional radiation therapy of malignant PTs is associated with nearly halving the local recurrence rate. 18 For borderline and malignant tumors an analysis of cases collected from the Rare Cancer Network between 1971 and 2003 showed that adjuvant radiotherapy yielded superior 10-year local control rates (86% with radiation versus 59% without radiation), but no survival benefit [20]. The NCCN guidelines (Version 1.2021) recommend adjuvant radiotherapy after primary resection only if additional recurrence would create significant morbidity, such as a chest wall recurrence following mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Metastasis is predominantly hematogenous to the lungs, bones, and viscera. 18,23 For phyllodes tumors, recurrence rates within the first 2-3 years of 10%-17%, 14%-25%, and 23%-30% are reported for benign, borderline and malignant tumors respectively. 17 The mean time to recurrence of benign, borderline, and malign PT's are reported as 20.2 ± 12.1, 16.9 ± 10.8, and 20.3 ± 19.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations